Programas de edición y la formación profesional en los estudiantes de la carrera de Comunicación Social de la Universidad Técnica de Babahoyo Extensión Quevedo, año 2019 - Jimenez Ruiz, Eddyn Emanuel (2020)
The editing programs are currently used by professionals and different media outlets that edit their work in audiovisual, written and other materials. But the learning of the manipulation or the handling of the different software is not part of the classes of the students of the Technical University of Babahoyo Quevedo extension. The syllables of the different subjects, learning theoretical and non-practical learning, theorists are fundamental in the students, but when entering their pre-professional practices, their laboratory managers ask if they know how to use any editing program, for the tool of the console of the radial cabin, to write in a model of a newspaper or to add images or audios in a video project. This project is carried out for the purpose of social communication students of the Technical University of Babahoyo Quevedo extension, they can take a professional edition course with programs used in different media and photography and publicize through this research, different programs that they should use that can teach them the manipulation of software used in the race. Teachers also attend a visit to a sound engineer, photographer, editor of a nearby newspaper in their syllables, so that students are curious about the use of editing programs and can enter different editing software manipulation courses that are offered in different cities of the country or in turn implement a laboratory predisposed to teach programs that help the learning of social communication students.